2017
DOI: 10.1007/s10964-017-0794-1
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Perspective on Reentry: Understanding the Causes and Consequences of Family Conflict and Peer Delinquency during Adolescence and Emerging Adulthood

Abstract: Despite the uniqueness of an incarceration experience for adolescents, there remains a shortage of research on adolescents and emerging adults who have been recently released from detention centers and are returning home during the transitional time period of "reentry". Drawing from the developmental literature, the current study uses a diverse (54% Black, 20% White, 26% Other Race) longitudinal survey of 337 male adolescents living in the United States to examine the interrelationships among crime, substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
(110 reference statements)
1
12
0
1
Order By: Relevance
“…Examining a large sample of returning adults, Boman and Mowen (2017) found that individuals who associated with criminally active peers were likely to offend themselves. Similar results were found among returning youth—association with delinquent peers was associated with increased offending and substance use (Mowen & Boman, 2018a). The notion that peers are criminogenic has been highlighted in other work as well (e.g., Abrams, 2007; Breese et al, 2000; Visher & Travis, 2003).…”
Section: Family and Peers During Reentrysupporting
confidence: 70%
“…Examining a large sample of returning adults, Boman and Mowen (2017) found that individuals who associated with criminally active peers were likely to offend themselves. Similar results were found among returning youth—association with delinquent peers was associated with increased offending and substance use (Mowen & Boman, 2018a). The notion that peers are criminogenic has been highlighted in other work as well (e.g., Abrams, 2007; Breese et al, 2000; Visher & Travis, 2003).…”
Section: Family and Peers During Reentrysupporting
confidence: 70%
“…Further complicating this situation is a possibility that is just being realized: Family and peer relationships may be mutually intertwined in the way that they relate to crime. In a recent article (Mowen & Boman, ), we found that high levels of family conflict may drive youth into deviant peer relationships as they undergo the transition between adolescence and emerging adulthood. Interestingly, elements of peer relationships had no impact on family relationships, suggesting that the causal path which leads to deviant peer associations may begin with negative aspects of the youth's family relationships.…”
Section: The Good the Bad And The Family And Peersmentioning
confidence: 91%
“…According to several authors (Basto-Pereira et al, 2015; Brame et al, 2018; Mowen & Boman, 2018; Schmidt et al, 2011), a comprehensive assessment of juvenile risk can predict not only juvenile recidivism but also criminal persistence into emerging adulthood. In fact, developmental research has shown that several outcomes (e.g., risk-taking behavior, impulsivity, or emotion regulation) of youth up to an age of 25 are more similar to younger adolescents than to adults (Arnett, 2000; Farrington et al, 2012).…”
Section: Introductionmentioning
confidence: 99%